2005
DOI: 10.1080/13607860412331310236
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the experiences of long-term care for residents with dementia, their relatives and staff

Abstract: Most older people living in 24-hour care settings have dementia. We employed qualitative interviews to explore positive and negative aspects of the experience of family carers, staff and people with dementia living in 10 homes in London and West Essex, selected to cover the full range of 24-hour long-term care settings. The interview used open semi-structured questions. We interviewed 21 residents, 17 relatives and 30 staff and five main themes were identified: Privacy and choice; relationships (abuse and vuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 18 publications
6
51
0
4
Order By: Relevance
“…There are highly significant statistical eISSN: 2357eISSN: -1330 Selection and peer-review under responsibility of the Organizing Committee of the conference differences (p=0,000) to X 2 =15,296 which suggests that the subjects who have experienced intense burden are more likely to manifest a depressive symptomatology. These results are in agreement with those found by Train et al (2005) and Dias (2011). In their opinion there is a strong relationship between high levels of burden and depressive symptomatology in caregivers who deal with mentally ill patients.…”
Section: Discussion/conclusionsupporting
confidence: 83%
“…There are highly significant statistical eISSN: 2357eISSN: -1330 Selection and peer-review under responsibility of the Organizing Committee of the conference differences (p=0,000) to X 2 =15,296 which suggests that the subjects who have experienced intense burden are more likely to manifest a depressive symptomatology. These results are in agreement with those found by Train et al (2005) and Dias (2011). In their opinion there is a strong relationship between high levels of burden and depressive symptomatology in caregivers who deal with mentally ill patients.…”
Section: Discussion/conclusionsupporting
confidence: 83%
“…van Baalen et al Gwyther, 1997;Heiser, 2002), and only two studies that reported the severity of the illness indicated that it was determined by the score on the Mini-Mental State Examination (MMSE) (Train, Nurock, Manela, Kitchen, & Livingston, 2005;Whitlach, Friss Feinberg, & Tucke, 2005). The type of dementia was only mentioned in two studies (Gwyther, 1997;Keady & Gilliard, 1999).…”
Section: Xmentioning
confidence: 99%
“…Research has shown, however, that residents with dementia still consider occupation to be important for their quality of life (Train et al, 2005;Dröes et al, 2006). Moreover, several studies show that occupation can have beneficial effects on the wellbeing of long-term care residents with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used explanations for limited activity programs are limited resources in terms of staff and finances. Both care workers and family caregivers often express the need for additional staff to engage residents in meaningful occupation (Train et al, 2005;Harmer and Orrell, 2008). Innes and Surr (2001) structurally observed active and inactive behavior of 76 residents with dementia over 269 hours, and found no relationship between staff ratio and the engagement of residents in occupational activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation